Circumferential pharyngeal reconstruction after total laryngopharyngectomy: A systematic review and network meta-analysis. (April 2022) - Costantino, Andrea; Festa, Bianca Maria; Ferreli, Fabio; Russo, Elena; Malvezzi, Luca; Giannitto, Caterina; Spriano, Giuseppe; Mercante, Giuseppe; De Virgilio, Armando
Highlights: Fistula and stenosis are relevant complications after total laryngo-pharyngectomy. The FJF has the lowest incidence of fistula after total pharyngeal reconstruction. The U-shaped PMMCF resulted in the lowest incidence of stenosis. The lowest incidence of feeding tube dependence was calculated for the FJF. The FJF seems the best option for circumferential pharyngeal reconstruction. Abstract: Objective: To compare the functional outcomes of different reconstructive techniques for circumferential pharyngeal reconstruction. Methods: A comprehensive electronic search was performed on PubMed/MEDLINE, Cochrane Library, and Google Scholar databases. Retrospective and prospective studies were included. Two independent reviewers extracted thirty-four studies after applying the eligibility criteria. An arm-based network analysis was conducted using a Bayesian hierarchical model. The main outcomes were pharyngo-cutaneous fistula (PCF) incidence, stenosis incidence and feeding tube dependence (FTD) incidence. Network estimates from outcome variables were presented as absolute risks, odds ratio [OR] with 95% credible intervals (CIs), and ranking probability. Results: A total of 1357 patients were included for 5 different interventions (tubed pectoralis muscle myocutaneous flap, t-PMMCF; tubed anterolateral tight flap, t-ALTF; tubed radial forearm free flap, t-RFFF; free jejunal flap, FJF; U-shaped pectoralis muscle myocutaneous flap, u-PMMCF). FJF showed a 92.8% chance of ranking first in terms of pharyngo-cutaneous fistula prevention (absolute risk: 10%), while the highest PCF incidence (42%) was measured for t-PMMCF. u-PMMCF showed the lowest absolute risk (11%) of stenosis incidence (62.2% chance of ranking first). t-PMMCF (5%), FJF (8%), and u-PMMCF (8%) showed similar results in terms of feeding tube dependence, with a 53.2%, 23.1% and 18.9% chance of ranking first, respectively. Conclusions: FJF seems to be the best reconstructive choice after total laryngo-pharyngectomy in terms of PCF, stenosis and FTD incidence. If this reconstructive method is not feasible, a u-PMMCF should be favored over tubed free and pedicled flaps. Further comparative studies are needed to confirm these results.